2011
DOI: 10.1111/j.1600-0781.2011.00631.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PUVA therapy on melanocytes and keratinocytes in non‐segmental vitiligo: histopathological, immuno‐histochemical and ultrastructural study

Abstract: Vitiligo affects both melanocytes and keratinocytes causing degenerative changes. These changes were present in both the leucodermic and the apparently normal perilesional skin. PUVA increases the number of active epidermal melanocytes in the three tested areas and recovers the melanocyte and keratinocyte degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 14 publications
(27 reference statements)
1
17
0
Order By: Relevance
“…Permanent oxidative disequilibrium caused by an intrinsic defect as in vitiligo skin may also prevent melanocyte regeneration and lead to a vicious circle. In fact, even if several studies revealed the presence of some melanocytes in depigmented skin, it is conceivable that the persistence of a hostile environment does not allow the complete return of functional melanocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Permanent oxidative disequilibrium caused by an intrinsic defect as in vitiligo skin may also prevent melanocyte regeneration and lead to a vicious circle. In fact, even if several studies revealed the presence of some melanocytes in depigmented skin, it is conceivable that the persistence of a hostile environment does not allow the complete return of functional melanocytes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the loss of melanocytes from vitiligo lesions is no longer considered complete, as several studies revealed the presence of some differentiated melanocytes in depigmented skin . It is unclear whether these sparse melanocytes have returned to the epidermis after the original injury, or whether a small population of intralesional cells remains . In the latter case, the physiology of such resilient melanocytes might inform us of intrinsic defense mechanisms that can prevent vitiligo.…”
Section: Melanocyte Lossmentioning
confidence: 99%
“…At present, it is believed that mature or activated melanocytes in the basal layer of epidermis released melanin granules by exocytosis, transformed to keratinocytes and migrated into stratum corneum (Vie et al, 2009;Anbar et al, 2012). During the migratory process of melanin into stratum corneum, a number of keratinocytes may control the type of melanin globule receptor so that skins accordingly show various colors (Valyi-Nagy et al, 1990;Minwalla et al, 2001).…”
Section: The Regulation Of Melanin Synthesis Of Taihe Silky Fowlmentioning
confidence: 99%